THE COMPARISON OF MENTAL HEALTH BETWEEN MALE ATHLETE AND NON-ATHLETE STUDENTS IN ISLAMIC AZAD UNIVERSITY BRANCHES OF GUILAN PROVINCE - Vahid Bakhshalipour,; Siavash Khodaparast Sareshkeh,; Zeinab Zivdar,; Nasrin Touba, (Sport Scientific And Practical Aspects, 2025)
Goals: Mental health is one of the most important aspects of evaluation of the health of different communities and it plays an important role in the assurance of the mobility and efficiency of every society. The purpose of this study was to compare mental health between male athlete and non-athlete students in Islamic Azad University Branches of Guilan Province. Method: this study is a descriptive and ex-post facto research. The statistic population was male students of Islamic Azad University Branches of Gilan Province. 480 students were randomly selected. The instrument of this study was General Health Questionnaire (GHQ-28). Data was analyzed by T-test and Chi-Square test. Results: anxiety subscale had the lowest score mean (3.51±3.02) in athlete students and social dysfunction had the lowest score mean (3.11±2.79) in non-athlete students. Depression subscale had the highest score mean in athlete (6.79±4.01) and non- athlete students (7.01±3.11). Conclusion: we can concluded that physical activities as an easy, inexpensive, and appropriate strategy and approach should be emphasized to increase mental health in students.